Ophirina amphinema n. gen., n. sp., a New Deeply Branching Discobid with Phylogenetic Affinity to Jakobids. Issue 1 (December 2018) - Yabuki, Akinori; Gyaltshen, Yangtsho; Heiss, Aaron; Fujikura, Katsunori; Kim, Eunsoo
Abstract We report a novel nanoflagellate, Ophirina amphinema n. gen. n. sp., isolated from a lagoon of the Solomon Islands. The flagellate displays 'typical excavate' morphological characteristics, such as the presence of a ventral feeding groove with vanes on the posterior flagellum. The cell is ca. 4 µm in length, bears two flagella, and has a single mitochondrion with flat to discoid cristae. The flagellate exists in two morphotypes: a suspension-feeder, which bears flagella that are about the length of the cell, and a swimmer, which has longer flagella. In a tree based on the analysis of 156 proteins, Ophirina is sister to jakobids, with moderate bootstrap support.Ophirina has some ultrastructural (e.g. B-fibre associated with the posterior basal body) and mtDNA (e.g.rpoA –D ) features in common with jakobids. Yet, other morphological features, including the crista morphology and presence of two flagellar vanes, rather connectOphirina to non-jakobid or non-discobid excavates.Ophirina amphinema has some unique features, such as an unusual segmented core structure within the basal bodies and a rightward-oriented dorsal fan. Thus, Ophirina represents a new deeply-branching member of Discoba, and its mosaic morphological characteristics may illuminate aspects of the ancestral eukaryotic cellular body plan.